REGIONAL ACTION UPDATE ON PACKWOOD TAX PLAN (Tufts Archival Research Center, 2007)
Update on the Packwood Tax Plan. Summarizes the general response from the tobacco industry to the plan. Lists the activities in different states with regard to the tax.